2004
DOI: 10.1373/clinchem.2003.028878
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Performance of Immunoassays for Drugs of Abuse Below Established Cutoff Values

Abstract: Background:The analytic performance and accuracy of drug detection below Substance Abuse and Mental Health Services Administration (SAMHSA) cutoffs is not well known. In some patient populations, clinically significant concentrations of abused drugs in urine may not be detected when current SAMHSA cutoffs are used. Our objectives were to define the precision profiles of three immunoassay systems for drugs of abuse and to evaluate the accuracy of testing at concentrations at which the CV was <20%. Methods: Drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 6 publications
0
18
0
1
Order By: Relevance
“…Most clinical laboratories still use the 300 ng/mL of morphine as the cutoff concentration for a positive opioid screen; however, the effectiveness of this cutoff concentration in the detection of intoxication or aberrant opioid use has not been rigorously evaluated in many clinical settings in which it is generally used. This threshold was also developed in adult populations and may not be appropriate for children who produce less concentrated urine [17]. Lower thresholds have been advocated in the pain medicine setting [18].…”
Section: Urine Screening For Opioidsmentioning
confidence: 99%
“…Most clinical laboratories still use the 300 ng/mL of morphine as the cutoff concentration for a positive opioid screen; however, the effectiveness of this cutoff concentration in the detection of intoxication or aberrant opioid use has not been rigorously evaluated in many clinical settings in which it is generally used. This threshold was also developed in adult populations and may not be appropriate for children who produce less concentrated urine [17]. Lower thresholds have been advocated in the pain medicine setting [18].…”
Section: Urine Screening For Opioidsmentioning
confidence: 99%
“…Hattab et al (2) did a similar study with lower cutoffs for cocaine, opiates and cannabinoids, and found that 74%, 84%, and 31% of cannabinoids, cocaine metabolites, and opiates, respectively, had a positive confirmation. This result underscores the importance of confirming presumed positive screen results when using a lower cutoff (6).…”
Section: Case Discussionmentioning
confidence: 62%
“…For infants and children presenting to an emergency department with altered mental status, suspected child abuse, burns, or other injuries, a urine drug screen is commonly used and provides results with a rapid turnaround time, despite lack of sensitivity and specificity (4). Adding to the difficulty in detection is the fact that if the urine is dilute, as it often is in children, the drug concentration will be even lower and less likely to be detected with the SAMHSA cutoffs (5,6).…”
Section: Case Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphetamine immunoassays display precise doseresponse properties from concentrations below the Substance Abuse and Mental Health Services Administration (SAMHSA)-stipulated cutoff to concentrations well above cutoff (8 ). Within this dynamic range, amphetamine and methamphetamine may exhibit dose-response properties that are distinguishable from other cross-immunoreactive compounds.…”
Section: © 2006 American Association For Clinical Chemistrymentioning
confidence: 99%